STUDI IMPLEMENTASI PROGRAM AFIRMASI MAHASISWA PAPUA DI PERGURUAN TINGGI NEGERI PROVINSI BALI - , ARDIAN BAKHTIAR ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This study aims to address the problem of non-optimal results affirmation of Papua students' academic achievement in public universities in Bali. This study uses a case study design, justified by questionnaire. Research subjects involving 36 students in Udayana University and 15 students in Ganesha University of Education. The study concluded that there are two factors that affect to affirmations Papua students' academic achievement. First, individual factors, namely, the prospective student academic achievement, expectations, adaptability, comfort motivation, preparation of learning and student effort in achieving learning outcomes. Secondly, environmental factors, namely, procedures, services, relationships among students, faculty treatment, and treatment of college education personnel affirmation higher education providers.